The Dynamics of Wayang Golek in Pandemic and Globalization: Traditional Art Sustainability - Islamy, Mohammad Rindu Fajar; Abdussalam, Aam; Adzkia, Giani (UIN Maulana Malik Ibrahim Malang, 2021)
This research aims to explore the dynamics of wayang golek art and to highlight its sustainability in the future. Modernity, the acceleration of technological devices and globalization wave in the last two decades, transfers great pressure on traditional arts and culture. Wayang Golek, a performing art originally from West Java, has recently received a fairly strong wave of resistance due to changes in the social culture which is mainly leading to modernity. By using a qualitative approach, data collection techniques were carried out by interviewing two main players as the puppeteers of Wayang Golek. The data analysis uses the theory of Miles and Hubberman, and the theoretical review of Islamic studies. The results of the study show that 1) Wayang Golek has unique characteristics, where the talent needed tends to go through the